Visualizing and labeling dense multi-sensor earth observation time series: The EO Time Series Viewer. (March 2020) - Jakimow, Benjamin; van der Linden, Sebastian; Thiel, Fabian; Frantz, David; Hostert, Patrick
Abstract: Multi-spectral spaceborne sensors with different spatial resolutions produce Earth observation (EO) time series (TS) with global coverage. The interactive visualization and interpretation of TS is essential to better understand changes in land-use and land-cover and to extract reference information for model calibration and validation. However, available software tools are often limited to specific sensors or optimized for application-specific visualizations. To overcome these limitations, we developed the EO Time Series Viewer, a free and open source QGIS plugin for user-friendly visualization, interpretation and labeling of multi-sensor TS data. The EO Time Series Viewer (i) combines advantages of spatial, spectral and temporal data visualization concepts that are so far not available in a single tool, (ii) provides maximum flexibility in terms of supported data formats, (iii) minimizes the user-interactions required to load and visualize multi-sensor TS data and (iv) speeds-up labeling of TS data based on enhanced GIS vector tools and formats. Highlights: User-friendly visualization and labeling of Earth observation time series in QGIS. Data-agnostic handling of multi-sensor time-series data. Simultaneous visualization of spatial, spectral and temporal features. Streamlined workflow for quick extraction and labeling of spectral-temporal features. Available as registered open source QGIS plugin.